Eine Syntax des "Novyj Margarit" des A. M. Kurbskij: Philologisch-dependenzgrammatische Analysen zu einem kirchenslavischen Übersetzungskorpus. - Bounatirou, Elias (Slavistische Beiträge., 2018)
"Novyj Margarit" is a collection of theological works which in all likelihood were translated from Latin into East Slavic-Church Slavonic under the direction of the Russian Prince Andrej Michajlovič Kurbskij (1528-1583). The collection was published for the first time in 1976ff. by Inge Auerbach. Elias Bounatirou now presents a dependency syntactic description of the language of "Novyj Margarit" based on the Wolfenbüttel handwriting. After an overview of the textual history of the collection and the method of linguistic analysis of historical texts, essential components of a grammar of "Novyj Margarit" are presented. The investigation leads to a revision of previous research on the Kurbsky language, which turns out to be less flawed than assumed. The study also represents a Latin research contribution: It contains a linguistic analysis (especially of graphic art and punctuation) of the most important translation of the "Novyj Margarit", the Latin Chrysostomus Edition Basel from 1558.